Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species - Macgowan, Iain (Zootaxa, 2018)
The Lonchaea polyhamata McAlpine, 1964 species-group is defined and five new species within it are described from the Afrotropical region namely, L. dama MacGowan sp. nov., L. mbeya MacGowan sp. nov., L. njombe MacGowan sp. nov., L. taita MacGowan sp. nov. and L. zomba MacGowan sp. nov. With the inclusion of the previously described L. polyhamata McAlpine, 1964 and L. teratosa McAlpine, 1964 the species group now comprises seven species, all from the Afrotropics.Afrotropical Lonchaea species which share character of 2 katepisternal setae with the L. polyhamata species group are also assessed. These include three new species namely L. aberdare MacGowan sp. nov., L. klynebergi MacGowan sp. nov. and L. muhavura MacGowan sp. nov. The male terminalia of the previously described L. dichaeta McAlpine, 1964 which also belongs to this wider group are illustrated for the first time.The male genitalia of all species are illustrated and a key to males of Afrotropical Lonchaea with two katepisternal setae is provided.